Tindakan Hukum Pelarangan Sopir Transportasi Online Dalam Menerima Penumpang oleh Taxi Lokal Dengan Kekerasan Fisik dan Verbal di Wilayah Hukum Polda Bali - Rai Bagus Cahyadi Wicaksana; I Nyoman Gede Sugiartha; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2024)
Public transport and transportation is very important to be able to realize transportation that meets the needs. Online transportation is a means of land transportation that is more efficient and effective. However, not everyone can accept the technological advances that occur. There are parties who refuse in terms of transportation; people feel rivaled by online ojek. The formulation of the problem in this study is 1) The impact of online transportation on local taxis 2) Criminal sanctions against local taxis who commit physical and verbal violence against online taxis. The research method uses empirical legal research. The results showed that the impact of online transportation on local taxis in Canggu is tight competition and difficulty getting passengers. In the provision of supporting facilities for transportation tourism, local residents have provided in each tourist area. Criminal sanctions against local taxis who commit physical and verbal violence against online taxis in their arrangements are not united in one special chapter, but are separated in certain chapters. In the Criminal Code, violent crimes can be classified as follows: Crimes against the life of another person Article 338- 350 of the Criminal Code.